COST ECONOMICS OF BREWERY WASTE IN JERSEY CROSSBRED DAIRY CATTLE UNDER FARMERS’ FIELD CONDITIONS - B. Rajesh Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to assess the cost economics of brewery waste in twenty four Jersey crossbred dairy cattle for one year with three treatments viz., control (T0), brewery waste (T1) and balanced ration (T2) in farmer’s field conditions with eight animals in each group. The control, brewery and balanced ration animals were fed as per traditional and standard feeding practices. Statistical analysis revealed a significant (P